ANALYSIS OF PALM SUGAR SUPPLY CHAIN WITH A FOOD SUPPLY CHAIN NETWORK APPROACH - Imelda Yunita; Farida Hanum Hamzah; Pramana Angga; Mhd Andri Kurniawan (Indonesian Journal of Agricultural Economics, 2022)
This study aims to determine the status of palm sugar supply chain in Rambah Tengah Barat Village, Rambah District, Rokan Hulu Province through an approach Food Supply Chain Network. The focus of the study was palm sugar production in Rambah Tengah Barat Village, Rambah District, Rokan Hulu Province. The research method is carried out in a purposive sampling,The data types used are primary data and secondary data. The study phase analyzed the palm sugar supply chain in Rambah Tengah Barat Village, Rambah District, Rokan Hulu Province through an approach Food Supply Chain Network starting from looking at supply chain objectives, existing supply chain structure, business processes down to resources in the brown sugar supply chain. The results show that the distribution model of the supply chain starts from farmers, collectors, retailers, stores and end consumers. Institutional strengthening among farmers is needed by forming groups of asphalt farmers to produce jaggery that can satisfy consumer demand. Production capacity is very limited and the use of technology is simple.